Proposal for Writing-teaching through Genres in Secondary Education - Boillos Pereira, Mari Mar (Didáctica. Lengua y Literatura, 2017)
New educational laws, as well as the methodological guidelines proposed by the different regional governments attest a concern for the development of students’ language skills. Among these concerns, emphasis must be placed on the interest for the development of the writing ability in Secondary school. Different studies urge to generate teaching interventions, such as the one in this article, to work on this skill from a communicative approach, and in a transversal way to all the subjects and not only to those linked to languages. This paper analyzes in detail the case of the El Salvador-Maristasschool (Bilbao). In this school, aware of the deficiencies in the teaching of writing, a framework has been generated for teaching this skill in Spanish in the first level of Secondary education. Once known the needs of the students and the official guiding principles, we present a didactic proposal based on the current studies on the teaching of writing. Specifically, we have selected the Genre-based approach as it meets the characteristics necessary to respond to the demands diagnosed and because it accomplishes official governmental guidelines. This proposal highlights the need to review existing models for the teaching of communicative skills and the need to create didactic intervention plans that anticipate the problems that have been witnessed in later educational stages.